Can you show me the process / steps to solve? 7-6a=6-7a

## solve 7-6a=6-7a

# 2 Answers

When working with equations such as this one you need to get all the variables(letters) on one side and the numbers on the other. You do this by adding the opposite of the value
**to both sides**. so...

7-6a = 6-7a

-6 = -6

1-6a= -7a

+6a= +6a

1 = -1a

-1 = a

To check this you would use -1 instead of a

7-6(-1) = 6-7(-1)

7+6 = 6+7

13 = 13

you have to bring all the numbers to one side of the equal sign and all "letter numbers" to the other by using the opposite signs preceeding them..so

7-6a = 6-7a

bringing the numbers to the other side of the equal sign

7-6 - 6a = -7a

1 - 6a = -7a

bringing the "letter numbers" to the other side of the equal sign

1= -7a+ 6a

1 = -1a

because we can't have a negative letter we multiply the equation by -1

thus

a =-1

checking to see if we are right by plugging in the answer of a = -1

7 - (6) (-1) = 6 - (7) (-1)

remembering the rule of multiplication of positive * negative signs= negative; and negative * negative = positive

7 + 6 = 6+ 7

13 = 13

all good.